PENGEMBANGAN MOBILE LEARNING MANAGEMENT SYSTEM BERBASIS WEBSITE UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA BELAJAR - Galih Yudha Saputra (Journal of Innovation Research and Knowledge, 2025)
The implementation of the Independent Learning Curriculum (Kurikulum Merdeka Belajar) has not been fully adopted by all schools due to a policy by the Ministry of Education allowing flexibility based on the readiness of teachers and educational staff. SMP Negeri 14 Samarinda is currently in transition from the 2013 Curriculum to the Independent Curriculum, which shifts the educational paradigm from teacher-centered to student-centered learning. This study aims to develop a website-based Mobile Learning Management System (MLMS) to support the implementation of the Independent Curriculum. The MLMS is expected to facilitate learning processes, accelerate evaluation, and serve as a database for learning module storage. The research method used is Research and Development (R&D), adopting the Rapid Application Development (RAD) model. System testing follows the ISO 9126 standard using Guttman and Likert scales. The results show that the functionality and portability aspects scored 1 (“Feasible”), usability reached 90% (“Excellent”), and reliability also scored 1 (“Feasible”). These results indicate that the developed system meets software quality standards and is suitable for supporting the implementation of the Independent Learning Curriculum